(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Paddy products have to go through a series of processes such as harvesting, threshing, packaging, bagging, transportation, storage, treatment and exchange prior to their arrival on the market, and as a number of studies across the country have shown, there are significant losses of rice production at all those stages Kerala, a state in southern India, produces only about five lakh tonnes of paddy out of a total annual need of about 25 lakh tonnes that is insufficient to feed the population. According to the report of the Ministry of Agriculture of Kerala about Rs 1,000 crore values of paddy products are imported into Kerala on an annual basis. Since a thousand crore company is under the industry, management of the current agricultural supply chain appears to be ineffective. This can be due to interference from middlemen. These issues have impacted farmers and consumers. The supply chain in Kerala is fragmented and involves many intermediaries such as distributors and dealers who gain maximum benefits. There are a lot of taxes on the inter-state supply chain. To function well, the supply chain needs professionals, but we do not have a skilled workforce in this field. Training and education in managing the supply chain is therefore necessary. This paper concentrate about the supply chain management of paddy in Kerala helps to understand the different channels in SCM, the obstacles in SCM, the issues and the spread of SCM prices.